Two-Photon Absorption Induced Single-Event Effects: Correlation Between Experiment and Simulation - Hales, Joel M.; Roche, Nicolas J.-H; Khachatrian, Ani; McMorrow, Dale; Buchner, Stephen; Warner, Jeffrey; Turowski, Marek; Lilja, Klas; Hooten, Nicholas C.; Zhang, En Xia; Reed, Robert A.; Schrimpf, Ronald D. (IEEE transactions on nuclear science, 2015)
Carrier-density distributions generated via two-photon absorption from pulsed laser excitation are simulated using nonlinear-optical beam propagation software. These simulated carrier-density distributions are used to calculate depth profiles of the integrated collected charge using a rectangular-parallel-piped approach for two silicon diodes of different structure. Using a set of proposed correlation metrics, the resulting simulated charge collection profiles are found to exhibit good agreement with measured transient charge-collection data for most, but not all of the metrics. The physical phenomena underlying the correlation metrics are discussed in detail. The remaining discrepancies that exist between the simulated and experimental results are addressed and their potential causes are detailed.